Reflections on the Prosperity Gospel - Adeleye, Femi B. (Sorrow & Blood: Christian Mission in Contexts of Suffering, Persecution, and Martyrdom, 2012)
On behalf of the WEA Mission Commission, William Carey Library is pleased to launch a landmark anthology and resource. This is a new publication in the Globalization of Mission series, Sorrow & Blood: Christian Mission in Contexts of Suffering, Persecution, and Martyrdom. The editorial team of William Taylor (USA), Tonica van der Meer (Brazil), and Reg Reimer (Canada) worked over four years to compile this unique resource anthology. This book is the product of the Mission Commission's global missiology task force and a worldwide team of committed colleagues and writers. Some 62 writers from 23 nations have collaborated to generate this unique global resource and anthology. Ajith Fernando of Sri Lanka and Christopher Wright of the UK each wrote prefaces to the book This latest WEA volume has the potential of profoundly shaping our approach to mission in today’s challenging and increasingly dangerous world.